Routine monitoring systems for integrated community case management programs: lessons from 18 countries in sub-Saharan Africa - Tanya Guenther; Yolanda Barberá Laínez; Nicholas P Oliphant; Martin Dale; Serge Raharison; Laura Miller; Geoffrey Namara; Theresa Diaz (Edinburgh University Global Health Society, 2014)
Implementing integrated community case management at scale involves thousands of diverse community health workers providing services in the hardest to reach, most deprived communities where formal services have failed to adequately deliver the most basic preventive and curative care - systems for routine monitoring must be designed to fit this context, place the end-user at the forefront,and align with the capacity for response.